A fatal case of transplantation-mediated alloimmune thrombocytopenia following liver transplantation. Issue 3 (16th March 2017) - Hill, Q. A.; Harrison, L. C.; Padmakumar, A. D.; Owen, R. G.; Prasad, K. R.; Lucas, G. F.; Tachtatzis, P.
ABSTRACT: Objective and importance: Transplantation-mediated alloimmune thrombocytopenia (TMAT) occurs when leukocytes transferred in a donor organ from a patient with immune thrombocytopenia (ITP), mount a response against recipient platelets. We present the first fatal case of TMAT following liver transplantation and review its aetiology and treatment. Clinical presentation: The liver donor had ITP and died from an intracranial haemorrhage. The recipient platelet count fell to 2 × 10 9 /l on post-operative day 2. Treatment refractory thrombocytopenia resulted in pulmonary haemorrhage and death. TMAT did not occur in a kidney recipient from the same ITP donor. Intervention: Extramedullary haematopoiesis was identified in the donor liver biopsy. Antibodies against platelet GPIb/IX were demonstrated in both donor and recipient. The thrombocytopenia was refractory to platelet transfusions, intravenous immunoglobulin, methylprednisolone, rituximab, romiplostim, plasmapheresis, vincristine and splenic artery embolization. On review of the literature, severe thrombocytopenia (<10 × 10 9 /l) has started within 3 days of transplantation in all reported TMAT cases. Serious non-fatal bleeding was observed in 3/5 previously reported cases. The optimal treatment is unclear. TMAT should resolve as donor lymphocytes are eliminated but re-transplantation may be required in severe refractory cases. TMAT has been reported in recipients of a liver but not kidney or heart transplant from ITP donors, probably because of the greater burden of co-transplanted lymphoid tissue. Conclusion: Before using the liver of an ITP donor, the recipient's fully informed consent is required. However, the risk of TMAT from an ITP donor is currently unknown and systematic review of donor registries is needed.